Quinoa (Chenopodium quinoa): A Promising Salinity Stress-Tolerant Crop for Diversification and Nutritional Security : Quinoa for diversification and nutritional security - Anureet Kaur; GK Dhillon; KS Sekhon (Journal of Soil Salinity and Water Quality, 2023)
Quinoa (Chenopodium quinoa Willd.) is a stress-bearing crop, able to grow in drought, salt-affected and low soil fertility areas and gaining importance for its nutritional quality. It is an excellent option for crop diversification and environmental protection. Quinoa grains contain saponin, a bitter compound that acts as a natural pesticide and insecticide for the grain. During consumption of quinoa, saponin can be easily removed by washing or soaking. It is mainly valued for its balanced protein content and lysine a limiting amino acid in most of cereals. It has been used as a functional ingredient in various food formulations to enhance the nutritional value of the product. Its gluten-free nature makes it an excellent choice for persons suffering from celiac disease. This article sheds a light on the production, nutritional and processing aspects of quinoa for promoting this as a future crop for food security.